2000
DOI: 10.1126/science.290.5498.1972
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Initiation of HCV RNA Replication in Cell Culture

Abstract: Hepatitis C virus (HCV) infection is a global health problem affecting an estimated 170 million individuals worldwide. We report the identification of multiple independent adaptive mutations that cluster in the HCV nonstructural protein NS5A and confer increased replicative ability in vitro. Among these adaptive mutations were a single amino acid substitution that allowed HCV RNA replication in 10% of transfected hepatoma cells and a deletion of 47 amino acids encompassing the interferon (IFN) sensitivity dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
1,315
8
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,325 publications
(1,380 citation statements)
references
References 19 publications
47
1,315
8
8
Order By: Relevance
“…By using transfection of the human hepatoma cell line Huh-7 with HCV replicons, it was found that these RNAs amplify only to low levels unless they acquire "cell culture adaptive" mutations. Many of these mutations cluster among others, in LCS I of NS5A, and they often reduce hyperphosphorylation arguing that this modification is of disadvantage for efficient RNA replication (8,45). In support of this assumption it was found that treatment of cells carrying non-adapted replicons with an inhibitor of the cellular kinase(s) responsible for NS5A hyperphosphorylation leads to an increase of RNA replication (46).…”
Section: Components Of the Hcv Replication Complexsupporting
confidence: 55%
See 1 more Smart Citation
“…By using transfection of the human hepatoma cell line Huh-7 with HCV replicons, it was found that these RNAs amplify only to low levels unless they acquire "cell culture adaptive" mutations. Many of these mutations cluster among others, in LCS I of NS5A, and they often reduce hyperphosphorylation arguing that this modification is of disadvantage for efficient RNA replication (8,45). In support of this assumption it was found that treatment of cells carrying non-adapted replicons with an inhibitor of the cellular kinase(s) responsible for NS5A hyperphosphorylation leads to an increase of RNA replication (46).…”
Section: Components Of the Hcv Replication Complexsupporting
confidence: 55%
“…However, some details begin to emerge due to the availability of efficient in vitro systems, most notably the HCV replicon system (7,8), HCV pseudoparticles (9, 10), and, very recently, the first system for efficient production of infectious HCV in cell culture (11)(12)(13). Since the minimum components required for HCV RNA translation and replication are the NTRs and the NS3 to NS5B coding region, in the following we will only refer to these viral elements.…”
Section: Components Of the Hcv Replication Complexmentioning
confidence: 99%
“…Introduction of these specific mutations in the wild-type consensus sequence significantly enhanced viral replication in vitro. [16][17][18][19][20] Mutational hot spots were found clustered primarily in the NS3, NS4B, and NS5A regions. The mechanisms behind the enhanced replication caused by these tissue-culture-adaptive mutations are still largely unknown, and the interesting fact that these mutations are not commonly found in patients suggests that these may have a toll on the viral fitness.…”
Section: Cell-based In Vitro Hcv Systemsmentioning
confidence: 99%
“…Subsequently, the Rice Lab identified several adaptive mutations in the HCV nonstructural protein NS5A. The new constructs conferred much increased replicative ability in vitro, as reported in 2000 (Blight et al, 2000). Continued search on HCV isolates with high in vitro replication efficiency yielded the most famous HCV cDNA clone, JFH-1 (genotype 2a).…”
mentioning
confidence: 95%